Repositioning and virgin coconut oil effleurage massage to reduce pressure ulcer risk among bedridden patients - Putriyani; Apriliani Yuliani Wuriningsih; Sri Wahyuni (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2026)
Background: Bedridden patients in the intensive care unit (ICU) are at increased risk of pressure ulcers because prolonged immobility and sustained pressure impair tissue perfusion and compromise skin integrity. Repositioning and effleurage massage are non-pharmacological nursing interventions that may help reduce this risk. Purpose: To evaluate changes in pressure ulcer risk following a combined repositioning and effleurage massage intervention among bedridden ICU patients. Method: This quasi-experimental study used a one-group pretest-posttest design and included 40 bedridden ICU patients recruited through total sampling. Pressure ulcer risk was assessed using the Norton Scale before and after a three-day intervention comprising repositioning every two hours and effleurage massage with virgin coconut oil. Pre-intervention and post-intervention risk scores were compared using the Wilcoxon signed-rank test. Results A marked shift toward lower pressure ulcer risk categories was observed after the intervention. The proportion of participants classified as being at high risk decreased from 70.0% (n = 28) before the intervention to 5.0% (n = 2) afterward, whereas the proportion classified as having no risk increased from 5.0% (n = 2) to 92.5% (n = 37). The Wilcoxon signed-rank test showed a statistically significant reduction in pressure ulcer risk following the intervention (p < 0.001). Conclusion: The combined repositioning and effleurage massage intervention was followed by a significant reduction in assessed pressure ulcer risk among bedridden ICU patients.